Pembrolizumab with Capox Bevacizumab in patients with microsatellite stable metastatic colorectal cancer and a high immune infiltrate: The FFCD 1703-POCHI trial. Issue 10 (October 2021) - Gallois, Claire; Emile, Jean-François; Kim, Stefano; Monterymard, Carole; Gilabert, Marine; Bez, Jérémie; Lièvre, Astrid; Dahan, Laetitia; Laurent-Puig, Pierre; Mineur, Laurent; Coriat, Romain; Legoux, Jean-Louis; et al.
Abstract: Pembrolizumab, a PD1 immune checkpoint inhibitor (ICI), was recently reported to be very effective in patients with microsatellite instable/deficient mismatch repair metastatic colorectal cancer (MSI/dMMR mCRC), unlike patients with microsatellite stable/proficient MMR (MSS/pMMR) mCRC, in whom ICIs are generally ineffective. However, about 15% of MSS/pMMR CRCs are highly infiltrated by tumour infiltrating lymphocytes. In addition, both oxaliplatin and bevacizumab have been shown to have immunomodulatory properties that may increase the efficacy of an ICI. We formulated the hypothesis that patients with MSS/pMMR mCRC with a high immune infiltrate can be sensitive to ICI plus oxalipatin and bevacizumab-based chemotherapy. POCHI is a multicenter, open-label, single-arm phase II trial to evaluate efficacy of Pembrolizumab with Capox Bevacizumab as first-line treatment of MSS/pMMR mCRC with a high immune infiltrate for which we plan to enrol 55 patients. Primary endpoint is progression-free survival (PFS) at 10 months, which is expected greater than 50%, but a 70% rate is hoped for. Main secondary objectives are overall survival, secondary resection rate and depth of response. Patients must have been resected of their primary tumour so as to evaluate two different immune scores (Immunoscore® and TuLIS) and are eligible if one score is "high". The first patient was included on April 20, 2021.